Enhancing peripheral nerve regeneration with neurotrophic factors and bioengineered scaffolds: A basic science and clinical perspective. Issue 4 (23rd September 2020) - Lien, Brian V.; Brown, Nolan J.; Ransom, Seth C.; Lehrich, Brandon M.; Shahrestani, Shane; Tafreshi, Ali R.; Ransom, Ryan C.; Sahyouni, Ronald
Abstract: Despite the peripheral nervous systems (PNS) capacity to regenerate, functional restoration is highly variable following peripheral nerve injury (PNI), oftentimes leading to persistent functional deficits. In the preclinical arena, advances in the therapeutic use of exogenous neurotrophic factors and synthetic neural scaffold technology hold promise in augmenting endogenous PNS regeneration following PNI. Clinical trials utilizing neurotrophic factors for other indications (eg, peripheral neuropathy) may provide insight into their role in PNI. Here we provide an updated review of progress made toward enhancing regeneration after PNI with a focus on neurotrophic factors and bioengineered scaffolds.